An Evaluation Of The Relationship Between Budget Deficits And External Debt: The Case Of Turkey And Spain - Cukurcayir, Sinan (European Scientific Journal, ESJ, 2016)
Budget deficit is an important economic problem subject that is emerging in today’s world, especially in many developed and developing national economies. Within this scope, as domestic resources are inadequate in the developing or underdeveloped national economies, these countries have to use several financing means in order to maintain economic growth and development. One of the most important one of these means is external debts. In this regard, external borrowing is an indispensable financial resource for today’s countries. In addition, financial integration movements accelerates many countries around the world who seek borrowing more easily. Hence, this leads to the creation of higher debt stock. At this point, the purpose of this study is to evaluate the relationship between budget deficits and external borrowing. In addition, it also aims to analyze the current data of Turkey and Spain economies.